Plasma Peptidylarginine Deiminase IV Promotes VWF-Platelet String Formation and Accelerates Thrombosis after Vessel Injury - Sorvillo, Nicoletta (Circ Res, 2019)
RATIONALE: Peptidylarginine deiminase type IV (PAD4), an enzyme essential for NET formation (NETosis), is released together with neutrophil extracellular traps (NETs) into the extracellular milieu. It citrullinates histone and holds the potential to citrullinate other protein targets. While NETosis is implicated in thrombosis, the impact of the released PAD4 is unknown. OBJECTIVE: This study tests the hypothesis that extracellular PAD4, released during inflammatory responses, citrullinates plasma proteins, thus affecting thrombus formation. METHODS AND RESULTS: Here we show that injection of r-huPAD4 in vivo induces formation of von Willebrand factor (VWF)-platelet strings in mesenteric venules, and that this is dependent on PAD4 enzymatic activity. VWF-platelet strings are naturally cleaved by a disintegrin and metalloproteinase with thrombospondin type-1 motif-13 (ADAMTS13). We detected a reduction of endogenous ADAMTS13 activity in the plasma of wild-type mice injected with r-huPAD4. Using mass spectrometry and in vitro studies, we found that r-huPAD4 citrullinates ADAMTS13 on specific arginine residues, and that this modification dramatically inhibits ADAMTS13 enzymatic activity. Elevated citrullination of ADAMTS13 was observed in plasma samples of patients with sepsis or non-infected patients who were elderly (e.g. age >65 years) and/or had underlying co-morbidites (e.g. diabetes, hypertension) as compared to healthy donors. This shows that ADAMTS13 is citrullinated in vivo. VWF-platelet strings that form on venules of Adamts13(−/−) mice were immediately cleared after injection of r-huADAMTS13, while they persisted in vessels of mice injected with citrullinated r-huADAMTS13. Next, we assessed the effect of extracellular PAD4 on platelet plug formation after ferric chloride-induced injury of mesenteric venules. Administration of r-huPAD4 decreased time to vessel occlusion and significantly reduced thrombus embolization. CONCLUSION: Our data indicate that PAD4 in circulation reduces VWF-platelet string clearance and accelerates formation of a stable platelet plug after vessel injury. We propose that this effect is, at least in part, due to ADAMTS13 inhibition.